Management of extensive facial injury resulting from canine bite in a pediatric patient: A clinical case report (Research, Society and Development, 2021)
Trauma in childhood and adolescence is an important factor in morbidity and mortality, being a huge public health problem. Among the facial traumas in children, animal bites stand out, mainly canine. And this type of injury results in complex facial trauma, which can have a functional and aesthetic involvement, as well as occurring in polymicrobial infections. Male patient, 8 years old, attended the Hospital da Restauração in Recife / Pernambuco, victim of a canine bite with extensive blunt lesion in the region of the labial commissure on the left side. The treatment instituted in this first moment was by suturing the entire wound and referring for rabies vaccination after three days. Post-operative guidelines were given for daily dressings, return in 10 days for suture removal, return for monitoring of rabies vaccination, rest for 10 days and oral hygiene guidance. The trauma caused by canine bite is defined as a public health problem that mostly affects the pediatric population. Thus, it is necessary to establish due attention to the treatment and follow-up of these patients, following the necessary care protocols, also promoting the control of potential complications that arise from injuries of this nature.